A New Protein Superfamily: TPPP-Like Proteins - Orosz, Ferenc (PLOS ONE, 2012)
The introduction of the term ‘Tubulin Polymerization Promoting Protein (TPPP)-like proteins’ is suggested. They constitute a eukaryotic protein superfamily, characterized by the presence of the p25alpha domain (Pfam05517, IPR008907), and named after the first identified member, TPPP/p25, exhibiting microtubule stabilizing function. TPPP-like proteins can be grouped on the basis of two characteristics: the length of their p25alpha domain, which can be long, short, truncated or partial, and the presence or absence of additional domain(s). TPPPs, in the strict sense, contain no other domains but one long or short p25alpha one (long- and short-type TPPPs, respectively). Proteins possessing truncated p25alpha domain are first described in this paper. They evolved from the long-type TPPPs and can be considered as arthropod-specific paralogs of long-type TPPPs. Phylogenetic analysis shows that the two groups (long-type and truncated TPPPs) split in the common ancestor of arthropods. Incomplete p25alpha domains can be found in multidomain TPPP-like proteins as well. The various subfamilies occur with a characteristic phyletic distribution: e. g., animal genomes/proteomes contain almost without exception long-type TPPPs; the multidomain apicortins occur almost exclusively in apicomplexan parasites. There are no data about the physiological function of these proteins except two human long-type TPPP paralogs which are involved in developmental processes of the brain and the musculoskeletal system, respectively. I predict that the superfamily members containing long or partial p25alpha domain are often intrinsically disordered proteins, while those with short or truncated domain(s) are structurally ordered. Interestingly, members of this superfamily connected or maybe connected to diseases are intrinsically disordered proteins.